Teaching Multiword Expressions in a Second-Language Context - Cecilia Owusu Debrah; Mohammed Issaka (Journal of Teaching and Learning)
The discussion on multiword expressions is an unavoidable aspect of any target language. Idioms, which are part of multiword expressions in the English Language, are viewed as one of the neglected areas in the second-language classroom. This study explored how teachers from the three main levels of education in two municipalities in the Bono Region of Ghana approached the teaching of idioms. This descriptive qualitative case study examined the resources available to teachers, assessing their preferences and awareness of approaches. The findings revealed that these instructors relied primarily on the core teaching materials and sometimes on other online resources for additional support. Due to changes in the curriculum, what emerged from the study is that idioms were not part of the content that was taught at the teacher-training colleges. These results also demonstrate a strong preference for traditional techniques because of familiarity and curriculum constraints. Teachers' awareness and usage of other methods, which are cognitively motivated, are limited. The implications could be linked to pedagogy, training, and resource constraints that teachers may face. It also highlights the necessity for curriculum adjustments to cater to the inadequacies. Addressing the identified concerns will improve the teaching and learning experience, to meet the approved standards, the expectations of teachers, and the needs of students. A focus on professional development programs tailored toward innovative teaching practices could address the training needs of educators and create more dynamic learning opportunities for learners.